The needs of collaborative tool for practicing pair programming in educational setting - Asnawi, Ani Liza; Ahmad, Amalina; Mohamed Azmin, Nor Fadhillah; Ismail, Kamsiah; Jusoh, Ahmad Zamani; Ibrahim, Siti Noorjannah; Mohd Ramli, Huda Adibah (International Association of Online Engineering (IAOE) Kirchengasse, 2019)
Pair programming is a technique which is introduced for helping programmers to develop high quality codes. Beside technical aspects, collaboration and working in team are the important skills needed in practicing the technique. These skills are essential to be instilled among our engineering students. Pair programming (known as PP) is one of Agile software development technique which introduces collaborative ways for programmers to develop software. Many advantages have been reported when one practiced the technique, which include improve team communication and productiveness, reduction in defect counts, and at the same time lessen development time. Among students, the technique was also reported to enhance students’ learning and satisfaction, as well as students’ learning skills. In order to get the full benefits of pair programming technique, however, correct guidance must be provided to the students. In this study, we proposed a collaborative pair programming tool for students in practicing the technique. The tool offers all features required to allow the collaboration for the pair programming technique to work. The tool is designed and developed using Visual Basic Studio software. A database is incorporated to store students’ information. An experiment was conducted to evaluate the students’ performance with and without using the tool. Results showed that the tool can help improving students’ performance in terms of quality of codes, and lessen their time in completing their coding. These are the consequences of collaboration and team work skills that they have been practicing when using the tool.